Self-Incompatibility in Brassicaceae: Identification and Characterization of SRK-Like Sequences Linked to the S-Locus in the Tribe Biscutelleae - Leducq, Jean-Baptiste (Genetics Society of America, 2013)
Self-incompatibility (SI) is a genetic system that prevents self-fertilization in many Angiosperms. Although plants from the Brassicaceae family present an apparently unique SI system that is ancestral to the family, investigations at the S-locus responsible for SI have been mostly limited to two distinct lineages (Brassica and Arabidopsis-Capsella, respectively). Here, we investigated SI in a third deep-branching lineage of Brassicaceae: the tribe Biscutelleae. By coupling sequencing of the SI gene responsible for pollen recognition (SRK) with phenotypic analyses based on controlled pollinations, we identified 20 SRK-like sequences functionally linked to 13 S-haplotypes in 21 individuals of Biscutella neustriaca and 220 seedlings. We found two genetic and phylogenetic features of SI in Biscutelleae that depart from patterns observed in the reference Arabidopsis clade: (1) SRK-like sequences cluster into two main phylogenetic lineages interspersed within the many SRK lineages of Arabidopsis; and (2) some SRK-like sequences are transmitted by linked pairs, suggesting local duplication within the S-locus. Strikingly, these features also were observed in the Brassica clade but probably evolved independently, as the two main SRK clusters in Biscutella are distinct from those in Brassica. In the light of our results and of what has been previously observed in other Brassicaceae, we discuss the ecological and evolutionary implications on SI plant populations of the high diversity and the complex dominance relationships we found at the S-locus in Biscutelleae.